#TikTokmademebuyit : En kvalitativ studie om hur reklam på TikTok påverkar användarnas attityder, konsumentbeteende och varumärkeskännedom. - Ottosson,Selma; Johansson,Sara (2023)
The following bachelor thesis aims to investigate how advertising on the social media application TikTok affects attitudes, consumer behaviour and brand awareness among their users aged 18-23 in Sweden. The ambition of the study is to contribute with research on how advertising is being recieved by TikTok's users, regarding attitudes and consumer behaviour, and establishing whether it is a successful marketing method to generate brand awareness. In order to conduct research on this topic, a qualitative approach was carried out using a research method with interviews as the primary source of the empirical evidence. The empirical material comes from six interviews, of which four female respondents and two male respondents. The study will also include other theoretical aspects on the topic with anchoring in previous research. The theoretical framework of the thesis consists of theories such as how we are influenced both subconsciously and consciously by advertising, models of consumer behaviour, user-generated content, word of mouth and lastly brand awareness. The results of the study showed that the users were not bothered by the large amount of advertising on TikTok but have a negative attitude regarding its credibility and quality, which has resulted in the consumers shopping through other platforms. Influencers however are more likely to influence consumers, due to word of mouth, even if there is a negative attitude towards influencers credibility. Instead, consumers prefer and trust user-generated content significantly more. Furthermore, advertising on TikTok does not affect users' consumer behaviour in the way of direct purchases. For some of the users, relevant advertising with the help of algorithms has encouraged consumption but also contributed to more selective and qualitative consumption. Lastly, companies that advertise on TikTok have mixed results on their brand awareness. It is possible for companies to achieve positive effects on brand awareness, provided that the advertising follows the culture of TikTok but also that the companies operate in an industry that is suitable for advertising on TikTok.
Keywords: TikTok; consumer behaviour; advertising; attitudes; brand awareness; user-generated content; word of mouth; algorithms; influencer marketing; infeed ads